STUDI PERTUMBUHAN BIBIT BALANGERAN (Shorea balangeran) DI SHADE HOUSE SETELAH MENGALAMI PENYIMPANAN DALAM KARDUS DAN PEMELIHARAAN DALAM SUNGKUP PLASTIK - Abdurrachman Abdurrachman; Basir Basir; Adistina Fitriani (Universitas Lambung Mangkurat, 2020)
The research aims to analyze the height anddiameter growth, and survivalpercentage of shorea balangeran seedlingsunder shade house after being kept in the cartons, and tended in the small greenhouse. The method used was a completerandom design. The results showed that the highest high growth of belangeran seedlings under the shadehousewas 3.25 cmthat was reached through the treatmens of keeping the seedlings for 6 days in the carton, and without tending in small green house. The highest diameter growth of belangeran seedlings under the shadehouse was 0.188 cm reached through the treatmens of keeping the seedlings for 9 days in the carton, and tending the seedlings in small green house for 15 days. All belangeran seedlings (141 seedlings) used during the research process were alive under the shade house with the percentage of 100%.